Early Pregnancy Hemoglobin A1C and Pregnancy Outcomes: A Population-Based Study - Chen, Lu; Pocobelli, Gaia; Yu, Onchee; Shortreed, Susan M.; Osmundson, Sarah S.; Fuller, Sharon; Wartko, Paige D.; Mcculloch, David; Warwick, Susan; Newton, Katherine M.; Dublin, Sascha (American Journal of Perinatology, 2019)
Objective Women with prediabetes are identified from screening for overt diabetes in early pregnancy, but the clinical significance of prediabetes in pregnancy is unclear. We examined whether prediabetes in early pregnancy was associated with risks of adverse outcomes.Study Design We conducted a retrospective cohort study of pregnant women enrolled in Kaiser Permanente Washington from 2011 to 2014. Early pregnancy hemoglobin A1C (A1C) values, covariates, and outcomes were ascertained from electronic medical records and state birth certificates. Women with prediabetes (A1C of 5.7–6.4%) were compared with those with normal A1C levels (<5.7%) for risk of gestational diabetes mellitus (GDM) and other outcomes including preeclampsia, primary cesarean delivery, induction of labor, large/small for gestational age, preterm birth, and macrosomia. We used modified Poisson's regression to calculate adjusted relative risks (RRs) and 95% confidence intervals (CIs).Results Of 7,020 women, 239 (3.4%) had prediabetes. GDM developed in 48% of prediabetic women compared with 11% of women with normal A1C levels (adjusted RR: 2.8, 95% CI: 2.4–3.3). Prediabetes was not associated with all other adverse maternal and neonatal outcomes.Conclusion Prediabetes in early pregnancy is a risk factor for GDM. Future research is needed to elucidate whether early intervention may reduce this risk.
Keywords: prediabetes; gestational diabetes mellitus; A1C; pregnancy; gestational weight gain